2017
DOI: 10.1017/s1368980016003517
|View full text |Cite
|
Sign up to set email alerts
|

Does breast-feeding reduce offspring junk food consumption during childhood? Examinations by socio-economic status and race/ethnicity

Abstract: Objective: To examine whether breast-feeding duration and socio-economic status (SES) interact to predict junk food consumption among offspring and whether the interaction differs across racial/ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…While a number of factors have been identified as influential in childhood obesogenic food consumption ( 37 , 38 , 46 , 47 ) , one potential modifiable risk factor that is typically overlooked is maltreatment – both psychological and physical. Our findings revealed that child maltreatment is significantly predictive of obesogenic food consumption and that these findings are largely driven by acts of physical maltreatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of factors have been identified as influential in childhood obesogenic food consumption ( 37 , 38 , 46 , 47 ) , one potential modifiable risk factor that is typically overlooked is maltreatment – both psychological and physical. Our findings revealed that child maltreatment is significantly predictive of obesogenic food consumption and that these findings are largely driven by acts of physical maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…a more comprehensive battery of food items, micronutrients). Still, other studies exploring child diet have employed a similar set of items to tap obesogenic consumption patterns in children ( 46 , 50 ) . Relatedly, details concerning parental dietary behaviours would have also been preferred, although we were able to control for a number of maternal factors that correlate with dietary behaviours, such as impulse control ( 51 ) , depression ( 52 ) and other health lifestyle behaviours that cluster with dietary intake (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly lower daily frequency of sweets intake at 24 to <60 mo of age among children who were fully formula fed compared with those who were fully breastfed was also unexpected. Prior studies have reported significant associations between longer breastfeeding duration and lower intake of junk food (fast food, soda, sweets, salty snacks) [ 48 ]. Reasons for this discrepancy between the present study and the prior study may be attributable to differences in the study population, with the present study being composed of primarily Hispanic children in Southern California, with all children living in low-income households and participating in WIC, in contrast to the prior study which used a nationally representative sample from the Early Childhood Longitudinal Study: Birth Cohort [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported significant associations between longer breastfeeding duration and lower intake of junk food (fast food, soda, sweets, salty snacks) [ 48 ]. Reasons for this discrepancy between the present study and the prior study may be attributable to differences in the study population, with the present study being composed of primarily Hispanic children in Southern California, with all children living in low-income households and participating in WIC, in contrast to the prior study which used a nationally representative sample from the Early Childhood Longitudinal Study: Birth Cohort [ 48 ]. The age of introduction of sweets did not differ significantly by infant feeding category in the WIC ITFPS-2 [ 20 ], and the amount of sweets consumed did not differ by breastfeeding duration in the IFPS-II [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between breastfeeding and diet has already been investigated at the level of food items and food groups. Some studies reported that a longer duration of any or exclusive breastfeeding was associated with a higher intake of fruits (43)(44)(45)(46) and vegetables (43)(44)(45)(46)(47)(48)(49)(50)(51) in children, while a lower consumption of processed foods and sugar-sweetened beverages (45,46,52,53) . However, in nutritional epidemiology, the reductionist approach, which only considers a https://doi.org/10.1017/S0007114522002057 Published online by Cambridge University Press particular food or food group, might not provide a comprehensive picture of dietary intake since people do not consume foods in isolation.…”
Section: Discussionmentioning
confidence: 99%